Is Smart Farming the Future of Sustainable Agriculture? Insights from a Village-Level Innovation Adoption - Hermiliana, Hermiliana; Tupas, Gerly-Ayn; Maksiri, Wanida (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the implementation of smart farming in Lapajung Subdistrict, Lalabata District, Soppeng Regency, and to examine how its application contributes to improving agricultural productivity in the area. Methodology: This study employed a qualitative approach with a descriptive case study design in Lapajung Sub-District, Soppeng Regency. Data were collected through observation, interviews, and documentation involving key informants. The data were analyzed using Miles and Huberman’s interactive model, guided by Rogers’ five indicators of innovation diffusion. Main Findings: Smart farming implementation in Lapajung Urban Village improved crop productivity, optimized water and fertilizer use, reduced pesticide dependency, and enhanced sustainability. Farmers reported time and labor savings, more accurate crop monitoring, and greater resilience to climate variability. Trial opportunities increased adoption rates. Despite challenges such as high initial costs and technical complexity, observable benefits encouraged wider acceptance and demonstrated strong alignment with local agricultural values. Novelty/Originality of this study: This study introduces an integrated educational approach to smart farming adoption in rural Indonesia by using Everett Rogers’ diffusion of innovation theory as a pedagogical framework. It contributes to the field of educational agricultural technology by highlighting how structured training, local compatibility, and observable outcomes can accelerate the understanding and acceptance of smart farming among farmers. This research uniquely bridges technological innovation with community-based agricultural education, promoting sustainable farming literacy.